Causing Factors of Improvement in the Value of Intranatal Care (INC) on the Passing of the Competence Test of D3 Midwifery Students - Firna, Fransiska; Syam, Aminuddin; Budu, Budu; Ahmad, Mardiana; Nontji, Werna; Usman, Andi Nilawati; Niar, Niar (Jurnal Ilmiah Kesehatan (JIKA), 2024)
One of the compulsory courses in the midwife curriculum is the INC course or Maternity care, where this course is a subject that combines theory and practicum, based on the syllabus where the course consists of 5 credits divided into 3 practical credits and 2 theoretical credits, because there was a change in the learning process due to the Covid-19 pandemic, the learning system was carried out during/online which had an impact on the GPA obtained by students and also had an impact on the results of the national competency exam, this can be seen from the decrease in GPA scores and graduation during the pandemic.The aim of this research was to find out the factors that cause a decrease in the value of the INC course on the graduation D3 Midwifery students. The method in this study was retrospective with a crosssectional study design to reveal a causal relationship. There were 69 female students who had not passed the Competency Test as Subjects in the D3 Midwifery study. Analysis to see the relationship used the Chi-Square test. The results of the study found a relationship between learning methods (p-value 0,05 <0,042), learning network (p-value 0,05<0,003)and learning location (p-value 0,05 <0,031)with the value of Intranatal Care to pass the competency test for D3 Midwifery STIKES Bina Generasi Polewali Mandar students. Conclusion, there is a relationship between learned networks, learned methods, learned location are a relationship between learned networks, learned methods, learned location.